Mayor Greg Goodnight : crisis in the U.S. auto industry - Bates, Lisa Tepper; Bagley, Constance E. ([London] : SAGE, 2016)
In December 2008, the Mayor of Kokomo, Indiana - Greg Goodnight - received the news that congressional leaders had failed to agree on terms for emergency federal financial assistance for the U.S. 'Big Three' automakers. Without some sort of substantial government intervention, at least one of the three - General Motors - seemed headed for almost certain and fairly immediate bankruptcy and possible cessation of operations. Mayor Goodnight's concern was that nearly one quarter of the Kokomo area's workforce was employed directly by the auto industry. This study examines his response to the crisis.
Originally Published in: Tepper Bates, L., & Bagley, C. E. (2009). Mayor Greg Goodnight: Crisis in the U.S. Auto Industry. 09-011. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Goodnight, Greg; Social responsibility of business -- Case studies; Crisis management -- Case studies; Kokoma (Ind.) -- Economic conditions